2013
DOI: 10.1121/1.4809679
|View full text |Cite
|
Sign up to set email alerts
|

Shear wave speed dispersion and attenuation in granular marine sediments

Abstract: The reported compressional wave speed dispersion and attenuation could be explained by a modified gap stiffness model incorporated into the Biot model (the BIMGS model). In contrast, shear wave speed dispersion and attenuation have not been investigated in detail. No measurements of shear wave speed dispersion have been reported, and only Brunson's data provide the frequency characteristics of shear wave attenuation. In this study, Brunson's attenuation measurements are compared to predictions using the Biot-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 25 publications
0
14
0
5
Order By: Relevance
“…The Biot-Stoll model is widely used and a useful tool to analyze the acoustic characteristics of water-saturated granular media. Kimura et al summarized the characteristics of the Biot-Stoll model and reported some comparisons between analytical and experimental results [11], [32], [33]. Let us briefly recall the main characteristics of the Biot-Stoll model (more detailed information on the Biot-Stoll model can be found in [3], [7], [8], [17], [18], and [32]).…”
Section: B Effective Medium Models (Em)mentioning
confidence: 99%
“…The Biot-Stoll model is widely used and a useful tool to analyze the acoustic characteristics of water-saturated granular media. Kimura et al summarized the characteristics of the Biot-Stoll model and reported some comparisons between analytical and experimental results [11], [32], [33]. Let us briefly recall the main characteristics of the Biot-Stoll model (more detailed information on the Biot-Stoll model can be found in [3], [7], [8], [17], [18], and [32]).…”
Section: B Effective Medium Models (Em)mentioning
confidence: 99%
“…A heuristic correction factor for attenuation, C a , was taken to fit the measured values of the shear wave attenuation to the calculated values. 4 The factor is defined as follows:…”
Section: Resultsmentioning
confidence: 99%
“…The measurement method is almost the same as that described in Ref. 4. The sample was placed in a cylindrical acrylic vessel with an inner diameter of 43 mm.…”
Section: Samples and Methodsmentioning
confidence: 99%
See 2 more Smart Citations